MgO+2HNO3=Mg(NO3)2+H2OMgO+2H(+)+2NO3(-)=Mg(2+)+2NO3(-)+H2OMgO+2H(+)+=Mg(2+)++H2OSO2 + 2HNO3(конц.) =H2SO4 + 2NO2 SO2 + 2H(+)+2NO3(-) =2H(+)+SO4(2-) + 2NO2 SO2 +2NO3(-) =SO4(2-) + 2NO2Li2CO3+2HNO3=2LiNO3+H2O+CO22Li(+)+CO3(2-)+2H(+)+2NO3(-)=2Li(+)+2NO3(-)+H2O+CO2CO3(2-)+2H(+)=H2O+CO2Ba(OH)2+2HNO3=Ba(NO3)2+2H2OBa(2+)+2OH(-)+2H(+)+2NO3(-)=Ba(2+)+2NO3(-)+2H2OOH(-)+H(+)=H2OHg + 4HNO3(конц.) = Hg(NO3)2 + 2NO2 + 2H2O Hg(0) + 4H(+)+4NO3(-) = Hg(2+)+2NO3(-) + 2NO2 + 2H2O Hg(0) + 4H(+)+2NO3(-) = Hg(2+)+ 2NO2 + 2H2O